Leader-Member exchange and superior-subordinate communication behavior: A case of a Malaysia organization - Mohamad, Bahtiar; Abu Bakar, Hassan; Herman, Iran (Universiti Utara Malaysia, 2004)
This paper attempts to test the quality of relationship between superiors and subordinates as indicated in leader-member exchange (LMX) theory on superior communication behavior The results of this study indicate that there are no significance differences between out-group and in-group members. However when in-group members were compared to mid-group members the result reveals significance differences between these two groups.